Attention matters: pitch vs. pattern processing in adolescence - Elyse S Sussman (Frontiers in Psychology, 2013)
From the moment we wake up, we are flooded with more sensory inputs than we can possibly process. Selective attention mechanisms serve to limit the sensory onslaught, while facilitating the ability to perform everyday tasks. However, not much is known about the typical development of selective attention mechanisms during childhood even though impairments of attention are commonly noted in neurodevelopmental disorders. The current study focuses on a transitional time in child development, adolescence, to determine in what way specific auditory tasks have a modulatory effect on underlying brain activity to facilitate behavioral goals. Neural mechanisms of selective attention were tested through auditory pitch and pattern perception, using a measure of event-related brain potentials (ERPs) called the mismatch negativity (MMN). Sounds with a regular five-tone pattern were presented in three conditions. The conditions differed only in how participants were instructed to listen to the sounds. Focus was either on the pitch of the sounds, the pattern of the sounds, or on a close-captioned movie. Even though the sound input was identical in all conditions, task-specific modifications were manifest in the MMN evoked by the deviant sounds embedded in the test sequences. The results demonstrate that in adolescence, as in adults, selective attention alters neural activity specific to performance goals, thus indicating specific neural adaptation modulated by behavior.